THE USE OF PROBLEM BASED LEARNING TO IMPROVE STUDENTS’ SPEAKING ABILITY (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2014)
Senior high school students are expected to have a good speaking skill, meanwhile their ability to speak English is very low especially in term of fluency. Therefore, teachers need an alternative method to teach speaking skill that is called Problem based Learning. The objective of this study is to know the application of problem based learning as teaching method in improving students’ speaking ability and students’ achievement in speaking English. The action research was carried out in some steps. Those steps were pre-elimination test, conducting the cycles starting with planning, acting, observing, reflecting, and post-test. As data collection instruments, I used observation sheets, questionnaire, interview, and self and peer assessment of the students. The implementation of this method was reflected in the classroom activity, students self and peer assessment, questionnaire, interview, and observation sheets. The result of the study showed that there were significant improvements of students’ speaking ability after being taught by problem based learning. They also enjoyed the activities in class by having a discussion, sharing, and cooperation with their friends. In addition, the students gave positive opinion, response, and interest toward the implementation of problem based learning method. Therefore, the students’ speaking ability was increased. Based on the result above, it can be concluded that this method gave positive contribution to the improvement of the students’ speaking ability. This method is beneficial to help the students to learn to speak English in more enjoyable way.